A CASE REPORT OF 23-YEARS-OLD YOUNG WOMAN WITH PERICARDIAL EFFUSION IN SYSTEMIC LUPUS ERYTHEMATOSUS DIAGNOSED WITH ECHOCARDIOGRAPHY AND CT-SCAN - Sidhi Laksono; Steven Philip Surya (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Pericardial effusion is not daily case in emergency room (ER). It has wide spectrum of etiologies and one of them are autoimmune diseases like systemic lupus erythematosus. PE in SLE patient could increase morbidity and mortality rate. The clinical manifestation and laboratory finding might not specific. Imaging modalities, such emergency echocardiography and CT scan, are important to diagnose Pericardial Effusion (PE) and evaluation beyond to the adjacent structures. We presented a 23 years-old female with diagnosis of systemic lupus erythematosus (SLE) and cardiac involvement of PE that diagnosed with imaging modalities echocardiography and CT scan. In this case, echocardiography is the most available and reliable imaging modality for pericardial effusion and CT usually obtain to try and clarify or to rule out the cause of an effusion rather than just to confirm the diagnosis.